2011
DOI: 10.4238/2011.november.8.4
|View full text |Cite
|
Sign up to set email alerts
|

Genes involved in glucose repression and oxidative stress response in the fission yeast Schizosaccharomyces pombe

Abstract: ABSTRACT.We looked for changes in gene expression and novel genes that could be involved in the interaction between glucose repression and oxidative stress response in the fission yeast, Schizosaccharomyces pombe, using a constitutive invertase mutant, ird11, which is resistant to glucose. BLAST analysis was made of the S. pombe genome database of cDNAs whose expression ratios differentially decreased or increased upon exposure to mild oxidative stress in this mutant compared to the wild type. Genes with this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
3
3
0
Order By: Relevance
“…All ird mutants and the wild-type strain exhibited resistance to oxidative stress when they were grown in glucose starvation or de-repressed conditions (Figure 1). These results supported our previous results related to ird11 studies (Suslu et al, 2011;Palabiyik et al, 2012). These findings imply an adaptive response to oxidative stress in these mutants and links between glucose sensing/signaling and the oxidative stress response.…”
Section: Resistance Of Ird Mutants Against Oxidative Stresssupporting
confidence: 82%
“…All ird mutants and the wild-type strain exhibited resistance to oxidative stress when they were grown in glucose starvation or de-repressed conditions (Figure 1). These results supported our previous results related to ird11 studies (Suslu et al, 2011;Palabiyik et al, 2012). These findings imply an adaptive response to oxidative stress in these mutants and links between glucose sensing/signaling and the oxidative stress response.…”
Section: Resistance Of Ird Mutants Against Oxidative Stresssupporting
confidence: 82%
“…The up-regulation of GPP1 in ∆ idh1/2 - acl but not in ∆ idh1/2 -pvtu could be due to the fact that the fatty acids accumulated in ∆ idh1/2 - acl strain but not in ∆ idh1/2 -pvtu strain. The MPG1 was involved in cell wall synthesis and it catalyzed alpha-D-mannose 1-phosphate to generate GDP-mannose [29]. The results from Figure 3 showed that the production level of D-mannose was higher in ∆ idh1/2 -pvtu and ∆ idh1/2 - acl strains, which was consistent with the increased protein expression level of MPG1.…”
Section: Discussionsupporting
confidence: 52%
“…In this context, phosphatase 1 guanyltransferase mannose is involved in oxidative stress in yeast [93], while isocitrate dehydrogenase is involved in cellular stress in Cryptococcus neoformans [94]. The glucose regulated protein 78 kDa is a membrane protein that is up-regulated in conditions of cellular stress and that can lead to cell cycle arrest [95].…”
Section: Discussionmentioning
confidence: 99%